Some Views on the Grounds for Rethinking the Doctrine of Ownership - Spasibo-Fateeva, Inna (Teisė, 2022)
The article looks at the possibility of to revise property regulation and property law doctrine. The author identifies the most important factors that may influence the evolution of property law and provides an assessment whether today’s conditions can change the content of property law and whether they are doing it. The article further discusses changes in the objects of property, the model of economic ties, the motivation of owners and the possibilities of implementing property law.